Analisis Pengaruh Non Performing Financing, Net Operating Margin, Financing to Deposit Ratio dan Bopo Terhadap Return on Equity pada Bank Umum Syariah di Indonesia Tahun 2017-2022: Penelitian - Nandang Munandar; Tri Wahyudi; Ali Jamaludin; Deni Saeful Rizal; Rafa Nursyahela (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of Non-Performing Financing, Net Operating Margin, Financing To Deposit Ratio and BOPO on Return On Equity at Sharia Commercial Banks in Indonesia in 2017-2022. The method used in this study is quantitative method. The type of data used is secondary data and is cross section and time series data. The population in this study is the financial statements of 14 Sharia Commercial Banks in Indonesia for 2017-2022. The sampling technique in this study was purposive sampling. The sample used is the Financial statements of 10 Sharia Commercial Banks in Indonesia for 2017-2022. The data analysis technique used is regression analysis of panel data processed through the eviews 10 application. The results of this study show that Non Performing Financing has a negative and significant effect on Return On Equity, Net Operating Margin has a positive and significant effect on Return On Equity, Financing To Deposit Ratio has no effect on Return On Equity, and BOPO has a negative and significant effect on Return On Equity, and simultaneously Non Performing Financing, Net Operating Margin, Financing To Deposit Ratio and BOPO affect Return On Equity. With an Adjusted R-squared value of 81.89%, the rest is explained by other variables that were not used in this study.